Auditory Nerve Fibers Excite Targets Through Synapses That Vary in Convergence, Strength, and Short-Term Plasticity - Cao, Xiao-Jie; Oertel, Donata (Journal of neurophysiology, 2010)
Auditory nerve fibers are the major source of excitation to the three groups of principal cells of the ventral cochlear nucleus (VCN), bushy, T stellate, and octopus cells. Shock-evoked excitatory postsynaptic currents (eEPSCs) in slices from mice showed systematic differences between groups of principal cells, indicating that target cells contribute to determining pre- and postsynaptic properties of synapses from spiral ganglion cells. Bushy cells likely to be small spherical bushy cells receive no more than three, most often two, excitatory inputs; those likely to be globular bushy cells receive at least four, most likely five, inputs. T stellate cells receive 6.5 inputs. Octopus cells receive >60 inputs. The N-methyl-d-aspartate (NMDA) components of eEPSCs were largest in T stellate, smaller in bushy, and smallest in octopus cells, and they were larger in neurons from younger than older mice. The average AMPA conductance of a unitary input is 22 ± 15 nS in both groups of bushy cells, <1.5 nS in octopus cells, and 4.6 ± 3 nS in T stellate cells. Sensitivity to philanthotoxin (PhTX) and rectification in the intracellular presence of spermine indicate that AMPA receptors that mediate eEPSCs in T stellate cells contain more GluR2 subunits than those in bushy and octopus cells. The AMPA components of eEPSCs were briefer in bushy (0.5 ms half-width) than in T stellate and octopus cells (0.8–0.9 ms half-width). Widening of eEPSCs in the presence of cyclothiazide (CTZ) indicates that desensitization shortens eEPSCs. CTZ-insensitive synaptic depression of the AMPA components was greater in bushy and octopus than in T stellate cells.